Oligomeric Forms of Human Amyloid-Beta(1–42) Inhibit Antigen Presentation - Gericke, Christoph; Mallone, Anna; Engelhardt, Britta; Nitsch, Roger M.; Ferretti, Maria Teresa (Frontiers in Immunology, 2020)
Genetic, clinical, biochemical and histochemical data indicate a crucial involvement of inflammation in Alzheimer’s disease (AD), but harnessing the immune system to cure or prevent AD has so far proven difficult. Clarifying the cellular heterogeneity and signaling pathways associated with the presence of the AD hallmarks beta-amyloid and tau in the brain, would help to identify potential targets for therapy. While much attention has been so far devoted to microglia and their homeostatic phagocytic activity, additional cell types and immune functions might be affected in AD. Beyond microglia localized in the brain parenchyma, additional antigen-presenting cell (APC) types might be affected by beta-amyloid toxicity. Here, we investigated potential immunomodulatory properties of oligomeric species of beta-amyloid-peptide (Aβ) on microglia and putative APCs. We performed a comprehensive characterization of time- and pathology-dependent APC and T-cell alterations in a model of AD-like brain beta-amyloidosis, the APP-PS1-dE9 mouse model. We show that the deposition of first beta-amyloid plaques is accompanied by a significant reduction in MHC class II surface levels on brain APCs. Furthermore, taking advantage of customized in vitro systems and RNAseq, we demonstrate that a preparation containing various forms of oligomeric Aβ1-42 inhibits antigen presentation by altering the transcription of key immune mediators in dendritic cells. These results suggest that, beyond their neurotoxic effects, certain oligomeric Aβ forms can act as immunomodulatory agents on cerebral APCs and interfere with brain antigen presentation. Impaired brain immune surveillance might be one of the factors that facilitate Aβ and tau spreading in AD.